2015
DOI: 10.1111/twec.12295
|View full text |Cite
|
Sign up to set email alerts
|

RTAs' Proliferation and Trade‐diversion Effects: Evidence of the ‘Spaghetti Bowl’ Phenomenon

Abstract: Abstract:This paper investigates the trade-diversion effects of regional trade agreements (RTAs), socalled "Spaghetti bowl" Phenomenon (SBP), in multilateral trade. The SBP is due to the proliferation of RTAs. Thus, I investigate the relationship between the number of RTAs concluded by a country and the additional trade value attributed to an RTA. Using bilateral trade data in a sample of 119 countries, from 1995 to 2012, my main finding reveals a negative tradeeffect between them, confirming the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Regional trade agreements are sweeping the multilateral trade system like wildfire (Sorgho, ), and to date, there are about 470 such agreements. It is likely that regional trade agreements will continue increasing especially in the current uncertainty surrounding the global trade environment.…”
Section: Introductionmentioning
confidence: 99%
“…Regional trade agreements are sweeping the multilateral trade system like wildfire (Sorgho, ), and to date, there are about 470 such agreements. It is likely that regional trade agreements will continue increasing especially in the current uncertainty surrounding the global trade environment.…”
Section: Introductionmentioning
confidence: 99%
“…Building on previous work (Pal, 2008;Sorgho, 2016;Ullah & Inaba, 2011) we argue that gains from RTAs are doubtful while the proliferation of RTAs has globally negative effect on trade. The simple existence of RTAs does not necessarily guarantee that multilateral trading system will be the next step.…”
Section: Most Favoured Nation (Mfn)mentioning
confidence: 58%
“…While Dai, Yotov, and Zylkin () find that the trade diverting effect of a new RTA does not depend on how many free trade agreements the country already has, other studies have found that RTA trade effects do depend on the number of agreements already in place. Sorgho () and Cheong, Kwak and Tang () both find that RTA trade effects are smaller if the country already has pre‐existing regional trade agreements. If the latter result is correct, then as countries sign new trade agreements, the trade diversion caused by each new trade deal will decline in importance.…”
Section: Which Countries Would Make the Ideal Rta Trading Partners?mentioning
confidence: 98%